GAMBARAN KARAKTERISTIK KELAINAN ASTIGMATISMA PADA ANAK USIA 2-15 TAHUN DI RUMAH SAKIT MATA MAKASSAR PERIODE TAHUN 2018-2022 - Febriel Sevdy; Andi Rachmi Patompo; Irwandi Rachman (RS Mata Makassar: Journal of Ophthalmology, 2024)
Astigmatism is a refractive error, which is a refraction in which condition the focal point of light cannot be formed on the retina. Astigmatism begins to be detected 68% when the child is 4 years old and 95% at the age of 7 years. This study aims to determine the characteristics of astigmatism disorders in children aged 2-15 years at the Eye Hospital of Makassar for the period 2018-2022. This research is descriptive retrospective. The sample collection technique was carried out using secondary data from the medical records of the Eye Hospital of Makassar. Based on the study, it was found that most astigmatism abnormalities based on age classification were dominated by children aged 11-15 years, namely 484 eyes (66.5%), gender classification obtained children who were female as many 484 eyes (66.5%), based on refractive status dominated by children with Compound Myopic Astigmatism (CMA) refractive status, totaling 523 eyes (71,9%). Based on the classification of initial vision (VOD), it was dominated by a vision of ≥20/150, totaling 195 eyes (26,7%). While the classification of initial vision (VOS) is also dominated by the same category of vision ≥20/150, totaling 193 eyes (26,5%). Based on the classification of the best vision after correction (OD) found in 20/20-20/25 vision, which amounted to 232 eyes (31,9%). While the classification of vision after correction (OS) is also dominated by the same category of vision 20/20-20/30 totaling 230 eyes (31,6%). Based on the lateralization classification, 638 eyes (77,9%) children with Oculus Dextra Sinistra (ODS) lateralization were found.